Buyers Perception towards Prawn Feed - A Study in West Godavari District, Andhra Pradesh - Naidu, B. V. R. (Indian Journal of Marketing, 2007)
In recent years, there has been considerable discussion about the ’marketing revolution’ and it centers around the need for modern marketing to be consumer oriented, to be concerned with the needs and wishes of the consumer. There are a number of reasons why the study of consumer behavior developed as a separate marketing discipline. Consumers are often studied because certain decisions are significantly affected by their behavior or expected actions. For this reason, consumer behavior is said to be an applied discipline. Such applications are said to exist at two different levels of analysis, the micro perspective and the societal perspective. The West Godavari District is the king pin of Aquaculture in Andhra Pradesh. Fish and Prawn farming has shown a spectacular growth in the area. Prawn culture has attracted more number of farmers with heavy investments in the rural Coastal belt, bringing a major up gradation in the rural economy of the area. The growth of prawn culture has received major set back due to lack of proper technical know how in feeding. Due to lack of technical and scientific knowledge farmers in this region are unable to take right decision at the time of choosing a particular brand of prawn feed. In this context an attempt has been made to study and examine the buyers/farmers preferences towards prawn feed in the district of West Godavari, Andhra Pradesh.